2007
DOI: 10.1213/01.ane.0000255074.96657.39
|View full text |Cite
|
Sign up to set email alerts
|

Hypercapnic Hyperventilation Shortens Emergence Time from Isoflurane Anesthesia

Abstract: The emergence time after isoflurane anesthesia can be shortened significantly by using hyperventilation to rapidly clear the anesthetic from the lungs and CO2 rebreathing to induce hypercapnia during hyperventilation. The device should be considered when it is important to provide a rapid emergence, especially after surgical procedures where a high concentration of the volatile anesthetic was maintained right up to the end of the procedure, or where surgery ends abruptly and without warning.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
40
0
2

Year Published

2010
2010
2021
2021

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 32 publications
(43 citation statements)
references
References 14 publications
1
40
0
2
Order By: Relevance
“…[3910] and Brosnan et al ., in a study on horses, concluded that hypercapnic hyperpnea decreases time to standing without influencing anesthetic recovery quality. [11]…”
Section: Introductionmentioning
confidence: 99%
“…[3910] and Brosnan et al ., in a study on horses, concluded that hypercapnic hyperpnea decreases time to standing without influencing anesthetic recovery quality. [11]…”
Section: Introductionmentioning
confidence: 99%
“…The relative longer recovery time from sevoflurane and isoflurane compared with desflurane can be overcome by, for example, augmenting minute ventilation on emergence. [9][10][11] It has been shown that as little as a two to threefold increase in minute ventilation, while avoiding hypocapnia (i.e., isocapnic hyperpnea), increases the rate of elimination of isoflurane compared with that of sevoflurane and desflurane in patients conventionally ventilated.…”
mentioning
confidence: 99%
“…Compared with these factors and the minute ventilation at emergence, the independent effect of anesthetic blood solubility on arousal is quite small. [9][10][11] By appropriately adapting other aspects of the conduct of the anesthesia, the anesthesiologist can tailor the anesthetic to the needs of the obese patient with any of the three common volatile agents so the patient may still be able to wake up equally rapidly in the operating room. …”
mentioning
confidence: 99%
See 2 more Smart Citations